Utilization of drainage water heat in flooded urban areas - Kovalenko, Yurii; Katkov, Mykhailo; Ponomarenko, Ievgenii; Malovanyy, Myroslav; Tymchuk, Ivan (Ecological Questions, 2022)
The possibilities of using drainage water from flooded urban areas as a source of energy for heat supply of buildings located in these areas were considered. The use of heating technological workflows based on the utilization of drainage water heat with heat pumps was substantiated. A method was developed for determining the required energy potential of drainage water and for determining technological characteristics of the proposed workflows. A comparative analysis of various workflows was carried out and the advantages of the water-to-water heat pump along with the heat-insulated flooring system over other heat supply workflows are shown.